Reinforcement Technology and Construction Technology of High Rise Building Structure - Xiaoming Lu, Liujun Fan (Forest Chemicals Review)
The stability of building structure and the importance of reinforcement technology seriously affect the safety of high-rise buildings. In this paper, based on an actual project, the reliability of the original structure before reinforcement is identified and analyzed. According to the results of reliability evaluation, some suggestions on the reinforcement design of the structure are put forward. According to the stress principle of the structure, the appropriate reinforcement form is selected and the reinforcement design is carried out. In this paper, the reinforced concrete nonlinear finite element analysis of the whole process of reinforcement is carried out for a typical frame beam in the project. This paper studies and summarizes the construction technology of structural reinforcement. Practice has proved that the effect of structural transformation is good.